STRENGTHENING TEACHER COMPETENCE IN ANALYSING QUESTION ITEMS AT SDIT DARUL ABROR, GARUT REGENCY - Rahardian, Dian; Rahayu, Ayu Puji; Nasrulloh, Iman; Budiman, Indra (LPPM STAI Muhammadiyah Probolinggo, 2025)
Learning assessment is an essential component of the educational process as it evaluates students’ achievement of competencies and provides a basis for improving instructional practices. However, evidence from the field shows that elementary school teachers still face challenges in conducting item analysis using quantitative approaches. This community service program was designed in the form of a workshop to enhance teachers’ conceptual understanding of learning assessment as well as their technical skills in item analysis using Anates software. The program was implemented through pre-test, lectures, hands-on practice, group discussions, and post-test activities involving 52 teachers, with 41 serving as research respondents. Data analysis using the Wilcoxon test indicated a significant difference between participants’ abilities before and after the workshop, with greater improvement observed in technical item analysis skills compared to conceptual understanding. These findings demonstrate that practice-oriented training supported by technology can effectively strengthen teachers’ competence in developing valid and reliable assessment instruments. The implications of this program extend beyond the partner school, offering a sustainable collaboration model between universities and elementary schools to foster teacher professional development.